Surgical Outcomes of 25-Gauge Trans-Conjunctival Sutureless Vitrectomy for Posterior Segment Disease - AAMIR AHMED YASIR ARAFAT, HUMA KAYANI (Journal of Fatima Jinnah Medical University, 2018)
Purpose: to evaluate the safety and efficacy of 25-gauge pars plana vitrectomy for posterior segment disease. Design: single centre, prospective, interventional case series. Participants: 24 eyes of 24 patients underwent 25-gauge pars plana vitrectomy at ophthalmology department of Sir Ganga Ram Hospital, Lahore from July 2010 to January 2012. Intervention: all eyes were operated using Alcon Accurus vitrectomy system and 25-gauge (Alcon) instruments. Materials and Methods: 24 eyes of 24 patients with posterior segment disease e.g vitreous hemorrhage alone (18 eyes) and combined vitreous hemorrhage with epiretinal membrane (6 eyes) were included in the case series. 25-gauge transconjunctival sutureless vitrectomy alone or combined with epiretinal membrane peeling was done in these respective cases, followed by fluid/ air exchange and post-operative pan-retinal photocoagulation. Main Outcome Measures: post-operative visual acuity, intraocular pressure, complication (intra-operative and post-operative) and any suturing of sclerotomy ports needed Results: Out of a total of 24 patients, 16 (66.7%) were males and 8 (33.3%) were females. 18 eyes (75%) had vitreous hemorrhage and 6 eyes (25%) had vitreous hemorrhage combined with tractional membranes involving macula. No intra-operative complication occurred and no case required conversion to 20-gauge vitrectomy. No suturing of any sclerotomy port was needed. The 25-gauge instruments were fragile. Bending of endoillumination probe was seen during the procedure but no breakage of any instrument took place. Peripheral vitreous shaving was difficult due to fragile instruments and indentation was required. Post-operative day 1 follow-up, visual acuity improved in 14 eyes (58.3%), reduced in 8 eyes (33.3%) due to recurrent vitreous hemorrhage and remained the same in 2 (8.3%) eyes. Day 7 follow-up showed further improvement in visual acuity from day 1 in 12 eyes and remained the same in 12 eyes. Final follow-up (3 months) showed visual acuity improvement in all patients from their pre-operative level. Subconjunctival hemorrhage was seen in 4 eyes (16.7%) which cleared spontaneously within a week’s time. Recurrent vitreous hemorrhage (6 eyes 25%) which was mild (blurred disc view) cleared within the follow-up period. Intra-ocular pressure remained within normal range throughout post-operative period. Conclusion: primary 25-gauge transconjunctival sutureless vitrectomy is an effective procedure in treatment of relatively uncomplicated posterior segment disease that requires minimal intraocular manipulation. It hastens postoperative healing.